Impact of Distal Ulnar Fracture Malunion on Distal Radioulnar Joint Instability: A Biomechanical Study of the Distal Interosseous Membrane Using a Cadaver Model - Satoshi Miyamura (2018)
© 2017 American Society for Surgery of the Hand Purpose Certain distal ulna fractures may contribute to distal radioulnar joint (DRUJ) instability. We hypothesized that residual distal ulna translation could affect DRUJ stability by slackening the distal interosseous membrane (DIOM). We aimed to test this hypothesis in a cadaver model. Methods We created an ulnar translated distal ulna fracture model in 6 cadavers. Dorsal and palmar displacements of the ulna relative to the radius were measured and DRUJ instability was staged under the following conditions: (1) 0-, 2-, and 4-mm ulnar translation of the distal ulna with an intact triangular fibrocartilage complex (TFCC) and DIOM; (2) 0-, 2-, and 4-mm translations with TFCC divided and an intact DIOM; and (3) a 0-mm translation with TFCC and DIOM divided. Results With an intact TFCC, dorsal and palmar displacements were not increased with any amount of distal ulna translation. After TFCC division with 0-mm translation, dorsal displacement increased significantly with DRUJ dislocation, whereas palmar displacement increased to a lesser extent with DRUJ subluxation. Palmar displacement gradually increased as the translation increased, and with 4-mm translation the ulnar head displaced to a perched position off the sigmoid notch. With TFCC and DIOM division, displacements increased markedly with DRUJ dislocation both dorsally and palmarly. Conclusions Dorsal dislocation occurred when the TFCC was divided regardless of the amount of distal ulna translation. Palmar subluxation occurred when the TFCC alone was divided. Palmar displacement to a perched position occurred because of slackening of the DIOM as a result of translation of the distal ulna. Bidirectional DRUJ instability with dorsal dislocation and palmar displacement to a perched position occurred when the TFCC was divided and the distal ulna was ulnarly translated. Clinical relevance Bidirectional DRUJ instability might occur when distal ulna translation deformity is associated with TFCC injury because the DIOM loses its function as a secondary stabilizer.